Innovation as an Agrotourism Competitive Excellence Strategy in Increasing Civet Coffee Product's Marketing Performance in Gianyar - Pande Ketut Ribek; I Gede Rihayana (AIBPM Publisher, 2019)
To increase sales of Luwak coffee agrotourism, the innovation strategy is in increasing the value of its sales. Through research entitled